2012
DOI: 10.1002/alr.21045
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution computed tomography analysis of the medial infratemporal fossa: a pilot study

Abstract: Average distance from the ANS to the AFO and BB was 78.5 mm and 83.2 mm, respectively. These measurements can be used by endoscopic skull base surgeons to guide dissection in the ITF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
(20 reference statements)
1
4
1
Order By: Relevance
“…mean ± SD of 80.3 ± 4.3 mm in males and 77.0 ± 6.5 mm in females) were comparable to our own findings (i.e. 80.2 ± 3.4 mm on the left and 80.4 ± 3.5 mm on the right in men; and 74.0 ± 3.1 mm on the left and 74.1 ± 2.9 mm on the right in women) 30 . However, Eloy et al did not find a statistically significant difference between the sexes regarding these measurements, whereas we found a clear sex difference for two of our four foramen ovale landmark measurements (i.e.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…mean ± SD of 80.3 ± 4.3 mm in males and 77.0 ± 6.5 mm in females) were comparable to our own findings (i.e. 80.2 ± 3.4 mm on the left and 80.4 ± 3.5 mm on the right in men; and 74.0 ± 3.1 mm on the left and 74.1 ± 2.9 mm on the right in women) 30 . However, Eloy et al did not find a statistically significant difference between the sexes regarding these measurements, whereas we found a clear sex difference for two of our four foramen ovale landmark measurements (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…distances from the posterior maxillary wall and from the anterior nasal spine). 30 This difference is unlikely to be explained by any sex difference in the shape of the foramen ovale itself. Ray et al examined the foramen ovale morphology and found no statistically significant differences between men and women, regarding size or shape.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The distance of the foramen ovale to the anterior nasal spine amounts to around 8 cm. Beside the lateral process, the buccal nerve may serve as guideline for identifying the foramen ovale [ 36 ], [ 146 ], [ 257 ], [ 263 ], [ 264 ], [ 265 ], [ 266 ], [ 267 ], [ 268 ]. Dorsal of the foramen ovale, the internal carotid artery is found in a distance of about 5 mm in the middle part of its petrosal segment [ 269 ].…”
Section: Basic Principles Of Rhino-neurosurgerymentioning
confidence: 99%